Análisis de la evolución de los recursos financieros transferidos a la Municipalidad Provincial de Maynas periodo 2016 - 2020 - Berrio Ortega, Jean Paul (2022)
Financial resources are all those public resources transferred by the Peruvian State to public entities at its three levels and other entities, with the purpose of being able to finance the public expenses included in its different activities for the fulfillment of the established objetives. This research is entitled “Analysis of the evolution of the financial resources transferred to the Provincial Municipality of Maynas, period 2016 – 2020”, and its general objective is to determine its evolution in the estudy period. Likewise, the research has been of a quantitative type and non-experimental descriptive design – cross - sectional. From the analysis and discussion of the results obtained, it has been possible to determine that the transferred financial resources show a positive evolution.